Prinsip Mu’asyarah Dalam Pola Relasi Keluarga Pengikut Jamaah Tabligh; Studi Lapangan Di Desa Wonodadi, Plantungan, Kendal - Khaidarullah (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2020)
The pattern of relationship between husband and wife of Tablighi Jamaat can be considered as academic anxiety. That is, it should be addressed in-depth understanding of the complexity of the entity they are in the middle of the post-modern era is now before make a justification to them. With a phenomenological approach and the perspective of Islamic Family Law, the focus of this article is to describe the behavior of religious people in a particular community which is empirically as objective reality, and put analysis as attitudes toward academic beings respond to people's religious behavior problems scientifically and proportionately.